al-Fikr al-siyasi al-Islami 'inda Hamid Rabi' (1925M-1989M) = Islamic political thought of Hamed Rabee (1925-1989 A.D.) / Sohaib Ali Jassim - Jassim, Sohaib Ali (2012)
This research aims at crystallizing and presenting the concepts of Islamic Political Thought of Hamed Rabee (1925-1989). He was an expert of political thought from Egypt. Amongst his philosophy is to revive the Islamic Political Inheritance or heritage (Turath) and his effort to reach to contemporary political theories that can help Islamic Ummah answers the many problems and questions facing Muslims around the world. This research depends mainly on the writings of Hamed Rabee and what is found about him. The research methodology is mainly library research with the descriptive analysis and the verification of the text. As the literature of the study was scattered in many books and articles of Hamed Rabee, The researcher intended to restructure Hamed Rabee's political thoughts and present them in the main text separated from any analysis or comparisons which were written mainly in the footnotes. The research consists of introduction, four chapters and research findings. It began with the life history of Hamed Rabee and his most important writings; which were classified according to different fields that show the encyclopedic knowledge of Rabee, which is reflected also in his integrative methodology of setting political theory in the light of different Islamic and social sciences. One of the main legacies of Rabee was paving the way for the establishment of a school of contemporary Islamic political thoughts and theories in Egypt. The research dealt also with his views on the Islamic Political heritage and its importance to political realities of the Ummah today; defining the reasons for the neglect of this aspect of Islamic legacy and the obstacles to the efforts to revive Islamic political inheritance. Rabee has also categorized the resources which students, political scientists and Muslim politician could refer to in their research or political life especially those who actively participate in any democratic process. The final chapter presents what Rabee refers to as the main pillars for formulating of Islamic Political Theory such as: political justice, moderation and reconciliation, the social nature of the Islamic political thought, the relation between thoughts, movements and real politics in the Islamic history and traditions, the Dawaah responsibility toward humanity. The research goes through twelve introductory principles and theoretical steps Rabee has come with from Islamic original resources and the practices of different Islamic systems throughout our history, that establish the bases for an applicable Islamic political theory. The research arrives in the end at what Hamed Rabee considers as characteristics or elements of the ideal model that he thinks should be implemented by Islamic government or Islamic System, which consist of: khilafah Concept, religious supremacy, unity of Muslim Ummah, Shuraa, implementing of Shariah as the internal legal system, justice, respecting human dignity and rejecting any form of discrimination, separation of centers of power and influence in the political structure, Jihad and the distinct foreign policy of the Islamic state, dominance of moral values and practices in all aspects of life, and finally religious legitimacy of the political system based on achieving the civilizational functions and responsibilities of the state.